Stability analysis of AC power system in the linear time periodic framework - Salis, Valerio (2019)
In recent decades, improvements in power electronics have led to a significant spread of grid-connected converters, both for AC and DC applications. These converters are often interconnected together into a complex, typically non-linear power system, where the interaction between harmonics at the various interfaces of the network can lead to unstable operation mode. Hence, the development of methods in order to perform stability analysis of power systems has been a challenging topic for researchers. The analysis of DC and balanced three-phase AC systems has been widely studied and precise methods have been developed. However, in the case of single-phase or unbalanced three-phase systems, the analysis is more complex and at the beginning of this project it was still an open field for research. Thus, with focus on the latter systems, this thesis presents the stability analysis approach derived in the Linear Time Periodic (LTP) framework. Given a general power system, this is split into a source and a load subsystem. At the point of common coupling, small-signal current injections are performed in order to measure the harmonic matrix impedances of source and load. Then, LTP Nyquist Criterion is applied to the ratio of the two harmonic impedances. This allows one to perform stability analysis of any system, without the requirement of knowing its structure or its parameter values. Hence this can be referred to as a "black-box approach". Furthermore, in order to provide a theoretical validation of the method, several systems have been analysed and their LTP models have been analytically calculated and validated through simulation and experimental results. The harmonic impedances have been experimentally measured using a so-called Stability-Measurement-Unit (SMU), which is an independent converter that performs small-signal current injections and records voltage and currents perturbations. The recorded data has been post-processed in Matlab to calculate harmonic impedances and LTP Nyquist. A precise stability boundaries identification has been obtained for all the analysed systems.